On the dimensions of waqf performance measurements: a survey - Md. Said, Zainol; Al-Shaghdari, Fahd Mohammed Obad; Ateik, Al-Harath; Aljounaidi, Abdoulrahman (Usuli Faqih Research Centre PLT, 2024)
Issues in waqf management have been extensively deliberated with concerns about whether they have been efficiently and competently managed in order to accomplish intended objectives of their stakeholders. Studies on the performance measurement of these organizations exposed the use of financial ratios as the dominant dimension in the measurements. It has been contended that because of their non-profit religious nature and because they are entrusted with assets for social and economic development of the society, their performance measurement should additionally measure dimensions related to and focussed on realization of their goals, missions and stakeholders’ objectives. In order to provide a framework of performance measurements that includes both financial and non-financial aspects, this research reports a survey of these extra performance measurement dimensions that have been suggested in the literature. In order to comprehend how non-profit organisations' (NPOs') non-financial performance aspects might be applied to waqf institutions' performance assessments, a literature analysis was conducted. The primary objective of this paper to compile an assortment of quantitative and qualitative measurement tools that may be customised for use in assessing waqf institutional performance. Besides, the main findings of this research are that the elements of effectiveness should be utilised in measuring the success and productivity of Waqf institutions. Also, the idea of waqf institution performance metrics based on financial and non-financial element of measurement is one of the study key findings. In addition to offering a substantial insight into the "available" dimensions of evaluating the performances of waqf institutions, it is hoped that this study will prove to be an informative collection of methodologies.